Pengembanga Model Pembelajaran Kelas Sumber (PKS) Untuk Meningkatkan Aktivitas Belajar Anak Autisme di Sekolah Dasar Inklusi - Sri Oenfiati, ; Sri Joeda Andajani, ; I Nyoman S, (Widya Cendika, 2010)
Abstract : The special purpose which would be achieved in 1 year this research was developing classroom resources learning model to increase autism childrens learning activity in the inclusion elementary school while the purpose of this research in the first year was to result in developing prototype of classroom resources learning model based audio and video to increase the autism childrens learning activity with the normal with setting class modification which was interactive, inspirative, challenge, joyful, and motivating in the class environment. This research then used development research. The model applied was Borg & Gall (1983) model through five steps with cycles as the following with 1 year; a) exploring and collecting the information which would be developed by; (1) study bibliography, and (2) study field, b) planning, this activity was to describe the early product of source class model by establishing the order of developing product; c) early developing product, i.e. arranging prototype of learning model of source class to increase autism childrens learning activity in the inclusion elementary school which was accompanied by media and the implementation direction; d) evaluating the validation of the main product outline, prototype learning model of classroom resources to increase the learning activity to autism children which was validated by the learning technologist, the expert of special education. This activity was to obtain input as the basic of prototype revision; and e) revising the main product outline, after comprehending the input from experts, then the writer revised the main product again in the form of prototype learning model of source class to increase the activity learning to autism children in the inclusion elementary school. The results of developing prototype acquisition of learning model of classroom resources to increase the learning activity of autism children which had been revised by learning technology and special education author were as the following: (1) learning model prototype of classroom resources based learning audio and video program which was interactive, inspirative, challenge, and motivating (I2M3) with setting class modification, (2) learning audio and video program in the form of VCD player by developing learning topic through two approaches i.e. thematic and subject matters.